Analisis Pengaruh TQM, Budaya Organisasi serta Sistem Penghargaan terhadap Kinerja Manajerial - Mardhiana, Putri; Yuliansyah, Yuliansyah; Puspita, Harsono Edwin; Dewi, Fajar Gustiawaty (Penerbit Goodwood, 2023)
Purpose: This study aims to evaluate the influence of Total Quality Management (TQM), Organizational Culture, and Reward Systems on managerial performance in startup companies in Indonesia during the COVID-19 pandemic. Methodology: This research considered a population of leaders/managers of service companies, with a total of 2,229 startup companies in Indonesia in 2021. Convenience sampling was used. In this case, 25 leaders and managers of start-up companies in Indonesia were the sample subjects., who answered the research questionnaire. This study was quantitative and used primary data. The primary data were obtained through field studies using questionnaires. The structural model in this study was measured using the coefficient of determination (R²) and the path coefficient to measure the relationship between variables. We then test the hypothesis using the t-test to determine the effect of the independent variable on the dependent variable. Results: it is known that Total Quality Management (TQM) and Organizational Culture have a significant positive impact on managerial performance in start-up companies in Indonesia. However, the Reward System has not been proven to have an impact on managerial performance in the context of start-up companies in Indonesia, perhaps due to the company's limitations in creating an effective reward system as a motivation for employees. Limitations: Limitations in this research include the use of a survey method with a questionnaire without direct interviews with respondents. The sample was limited to 13 startup companies using a convenience sampling method due to time constraints and the impact of the COVID-19 pandemic, as well as the low return rate for questionnaires due to the lack of research permits due to the COVID-19 pandemic. Contribution: This research is expected to provide a deeper understanding of the role of factors in research in facing the challenges faced by start-up companies in Indonesia today. Novelty: novelty in this research includes the use of new variables that have not been studied before and were carried out during the Covid-19 pandemic which provides a better picture from the worker's perspective.